Air pollution with exhaust particles at four metro construction sites in Copenhagen (Copenhagen, 2012)
"The main objectives were to measure and assess work related exposure of employees to ultrafine particles from construction equipment and to measure and assess possible pollution of the external environment outside four metro construction sites in Copenhagen. ..."